Design and Implementation Of Expert Advisor on Percentage Risk Money Management Using Supertrend and RSI Indicators on the USD/SGD Pair in MetaTrader 5 : Penelitian - Rehulina Dahinta Ketaren; Haikal Rahman; Dita Eka Pertiwi Sirait (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research designs and evaluates an Expert Advisor (EA) for trading by automating a strategy based on the Supertrend and RSI indicators, integrated with a Percentage Risk Money Management system. Using a Research and Development method with the Agile-Scrum model, the EA was implemented on MetaTrader 5 for the USD/SGD currency pair. It was tested through a five-year backtest (2020-2025) and a one-month real-time test on the H1 and H4 timeframes. The results show that the EA was able to generate profit on both timeframes, with optimal performance on H4 (profit factor of 1.69, maximum drawdown of 7.92%), while H1 showed profitability with higher risk (maximum drawdown of 16.97%). The EA successfully identified market trend direction and momentum objectively while applying disciplined risk management through dynamic lot sizing, stop loss, and take profit. The research concludes that the integration of Percentage Risk Money Management with the Supertrend and RSI indicators within an EA is an effective approach for automating USD/SGD trading, offering practical contributions to systematic risk management and academic contributions to the development of algorithmic trading systems.